2017
DOI: 10.1155/2017/4064156
|View full text |Cite
|
Sign up to set email alerts
|

Tangshen Formula Attenuates Colonic Structure Remodeling in Type 2 Diabetic Rats

Abstract: Aim. This study investigated the effect and mechanism of the Chinese herbal medicine Tangshen Formula (TSF) on GI structure remodeling in the rat model of diabetes. Methods. Type 2 diabetic rats were used. Wet weight per unit length, layer thicknesses, levels of collagens I and III, nuclear factor kappa B (NF-κB), interferon-γ (IFN-γ), interleukin-6 (IL-6), transforming growth factor-β1 (TGF-β1), and Smad2/3 expression in the rat colon were measured. Results. Compared with the control group animals, wet weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Our previous study has demonstrated that Tangshen Formula could partly attenuate colonic structure remodeling in type 2 diabetic rat model [ 23 ]. However, that study did not analyze the biomechanical properties and did not include small intestinal segments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study has demonstrated that Tangshen Formula could partly attenuate colonic structure remodeling in type 2 diabetic rat model [ 23 ]. However, that study did not analyze the biomechanical properties and did not include small intestinal segments.…”
Section: Discussionmentioning
confidence: 99%
“…In GK diabetic rat (another spontaneous type 2 diabetes model), intestinal histological [ [38] , [39] , [40] ] and biomechanical [ 39 , 40 ] remodeling has been reported, and similar data were obtained as STZ-induced diabetic rat model. Recently, our group has demonstrated the histological remodeling of colon such as wet weight and layer thicknesses increasing in high fat feeding plus low dose STZ-induced type 2 diabetic rat model [ 23 ]. However, to the best of our knowledge, no study in relation to histological and biomechanical remodeling of GI tract has been reported in world-widely used ZDF type 2 diabetic model so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[106][107][108] Mechanistic research has revealed that the Tangshen formula can promote hepatic lipid autophagy, alleviate hepatic steatosis by regulating the AMPK/SIRT1 pathway, [109] and reduce renal lipid deposition by promoting cholesterol efflux through regulating the PGC-1a/LXR/ ABCA1 pathway. [110] The Tangshen formula has significant therapeutic effects on multiple organ damage, [111] including the treatment of fatty liver, [109] improvement of gastrointestinal dynamics, [112] and reduction of myocardial fibrosis while fighting renal fibrosis. [113]…”
Section: Advantages and Advances In Mechanism Ofmentioning
confidence: 99%